Immune effects of surgical menopause and estrogen replacement therapy in peri-menopausal women - Kumru, S; Godekmerdan, A; Yilmaz, B (Elsevier Sci Ireland Ltd, 2004)
The complex relationship between sex hormones and immune function suggests that sex hormone deficiency and estrogen replacement therapy (ERT) in post-menopausal women may have pleiotropic effects on immune function. For this reason, we aimed to investigate short-term effects of surgical menopause and ERT on immunity profile in peri-menopausal women. Seventeen healthy peri-menopausal women who were to undergo total abdominal hysterectomy and bilateral salpingo-oopherectomy (TAH + BSO) for uterine myoma were enrolled into this study. Three blood samples were collected from each patient: 1-day prior to surgery, 30 days after the operation (before ERT) and 30 days after transdermal ERT. The percentages of peripheral blood lymphocyte subpopulations, serum interleukin-4 (IL-4) and interferon-gamma (IFN-gamma) concentrations were determined by flow-cytometry and ELISA, respectively. Following TAH + BSO, the percentage of CD8(+) cells was increased (P < 0.001) while the percentage of CD19(+) cells, serum IL-4, and IFN-gamma concentration and the ratio of CD4(+) to CD8(+) cells were decreased (P < 0.001, P < 0.001, P < 0.002, and P < 0.05, respectively). After ERT, this trend reversed and a decrease in the CD8+ cells (P < 0.001), increase in the CD19(+) cells percentages (P < 0.02) and increase in serum IFN-gamma concentration (P < 0.002) were observed. Although an increasing trend in the CD4(+) to CD8(+) ratio occurred by ERT, this was not significant. However, the decrease in the serum IL-4 concentration after TAH + BSO was not reversed by ERT. Hormone deficiency in post-menopausal women may cause an impaired immune response, and ERT can restore this phenomenon. Estrogen seems to have an important role in the regulation of immune function. (C) 2004 Elsevier Ireland Ltd. All rights reserved.
Keywords: menopause; estrogen replacement therapy; lymphocyte; IL-4; IFN-gamma